STUDI NEGARA ASEAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY MEDIASI PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Indra Sulistiana; Istianingsih Istianingsih (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This research aim to analyze influence of Good Corporate Governance toTax AvoidancewithCorporate Social Responsibility Disclosure as a intervening variable(Case Study on The Association of Southeast Asian Nations(ASEAN) Countries. Technique sampling is purposive sampling. The research is conducted on the TOP 50 of Manufacturingcompaniesin The Association of Southeast Asian Nations(ASEAN) Countries (2014-2015) range of time. The estimation model being used is multiple regression analysis.The purpose of this study was to determine are Good Corporate Governancehave an influence on Tax Avoidanceand is Corporate Social Responsibility Disclosureable to mediate the relationship Good Corporate Governanceto Tax Avoidance. The study involved trivariables, which is, one dependent variable, oneindependent variables and one variable of moderation. The dependent variable in this study was Tax Avoidance. The independent variables in this study are Good Corporate Governance, and Corporate Social Responsibility Disclosureas a interveningvariable.Keywords : Good Corporate Governance, Tax Avoidance, Corporate Social Responsibility Disclosure.